Anemia Prenatal is A Risk Factor for Postpartum Hemorrhage - MA RIFAH, ASIROTUL; PUII SURYANTINI, NANING (Kirana Publisher (KNPub), 2023)
Postpartum Hemorrhagic is still the main cause of maternal death. While anemia is a major contributor to maternal morbidity, therefore, to prevent Postpartum Hemorrhagic (PPH), it is important to be aware of the occurrence of anemia during pregnancy. The purpose of this study was to determine the relationship between anemia in pregnancy and postpartum hemorrhagic events at the Sukodono Health Center, Sidoarjo. This research is an observational study with a cross sectional approach. The population in this study was 125 respondents, a sample of 42 respondents was obtained using purposive sampling technique. Data collection used secondary data (medical records January - December 2022). Data were analyzed using the Fisher's Exact Test statistic with a significance level of α (0.05). The results showed that the ρ-value = 0.008, meaning that ρ (0.008) < α (0.05) or H1 is accepted: there is a relationship between anemia in pregnancy and the incidence of postpartum hemorrhagic (PPH) at the Sukodono Health Center, Sidoarjo Regency. Pregnancy with anemia in the third trimester has a high risk of experiencing Postpartum Hemorrhagic, so it is necessary to increase awareness of anemia by optimizing integrated antenatal care services.